The impact of a supportive supervision intervention on health workers in Niassa, Mozambique: a cluster-controlled trial - Tavares Madede; Mohsin Sidat; Eilish McAuliffe; Sergio Rogues Patricio; Ogenna Uduma; Marie Galligan; Susan Bradley; Isabel Cambe (BMC, 2017)
Abstract Background Regular supportive supervision is critical to retaining and motivating staff in resource-constrained settings. Previous studies have shown the particular contribution that supportive supervision can make to improving job satisfaction amongst over-stretched health workers in such settings. Methods The Support, Train and Empower Managers (STEM) study designed and implemented a supportive supervision intervention and measured its' impact on health workers using a controlled trial design with a three-arm pre- and post-study in Niassa Province in Mozambique. Post-intervention interviews with a small sample of health workers were also conducted. Results The quantitative measurements of job satisfaction, emotional exhaustion and work engagement showed no statistically significant differences between end-line and baseline. The qualitative data collected from health workers post the intervention showed many positive impacts on health workers not captured by this quantitative survey. Conclusions Health workers perceived an improvement in their performance and attributed this to the supportive supervision they had received from their supervisors following the intervention. Reports of increased motivation were also common. An unexpected, yet important consequence of the intervention, which participants directly attributed to the supervision intervention, was the increase in participation and voice amongst health workers in intervention facilities.